Prediksi Aktivitas Antikanker Babandotan dengan Pendekatan Kimia Medisinal dan Komputasi In Silico - Nazwa Cahya Kamila; Saeful Amin; Ai Sriwahyuni; Azzindani Januar (Pusat riset dan Inovasi Nasional, 2025)
This research aims to explore the potential of secondary metabolites from babandotan plant (Ageratum conyzoides L.) as breast cancer drug candidates through a medicinal chemistry approach using in silico studies. Breast cancer has the highest prevalence among women in Indonesia, with conventional treatments often causing serious side effects, prompting the search for new anticancer agents from natural sources. Babandotan plant (Ageratum conyzoides L.) has been empirically proven to have cytotoxic effects against cancer cells and possesses various pharmacological activities with anticancer potential based on its bioactive compounds such as flavonoids, terpenoids, alkaloids, and sterols.